Cutaneous anthrax complicated by necrotizing fasciitis and compartment syndrome - Muñoz-Ayala, Marissa Pamela (2013)
Introduction: Cutaneous anthrax is a zoonosis caused by Bacillus anthracis characterized by painless necrotic ulcer that usually heals spontaneously and without complications. The case of a farmer and cattle breeder male patient who presented a bullous serosanguineous ulcer surrounded by necrotic lesions in the ventral right forearm and multiple purulent satellite vesicles associated with extensive edema and disabling pain in the affected limb is reported. On admission, examinations revealed leukocytosis (15 000/mL), total CPK (1 730 U/L) and positive test for Bacillus anthracis by polymerase chain reaction (PCR). Compartment syndrome was diagnosed and emergency fasciotomy was performed. Surgical report was necrotizing fasciitis by finger test. Mild Volkmann ischemic contracture was found during follow-up. Diagnosis of compartment syndrome should be considered when disabling pain is present to decide prompt surgical intervention in order to avoid losing the limb involved.